Desensitization is an essencial part of your patient protocol at the dental appointment - Symonenko Р. В.; Vasil’yeva-Katashynskaya Н. Н. (Actual Dentistry, 2020)
Summary. The process of eliminating hyperesthesia of hard dental tissues is a standard method of pathogenetic treatment in conservative dentistry. Patients of almost all age groups are faced with increased tooth sensitivity (hypersensitivity) and in most cases it is one of the symptoms of other pathologies.This is the reason for the constantly growing interest of scientists and clinicians in the problems of desensitization of teeth, which is undoubtedly is the firststep in the rehabilitation process for patients with various dental pathologies. Features, hyperesthesia of hard dental tissues requires etiotropic treatment. However, we have the opportunity to influence the pathogenetic link and eliminate the significant symptoms of the disease by reducing dentinal permeability (minimizing the hydrodynamic processes that cause a painful reaction) directly at the dental appointment. Desensitizers and fluoride-containing agents are very effective in solving this problem. There is no doubt that the dentist needs to be well versed in the active ingredients of desensitizing agents, their mechanisms of action, significant advantages and indications for use. There is no universal remedy. Some patients need more than one type of treatment at the same time. Our extremely positive and long-term experience of using the medications of the VOCO company (Germany) will help to make unquestionable and right choice of drugs to eliminate dental hyperesthesia.